A CGE approach to measuring the impacts of EU structural funds in a small open economy. (2nd October 2014) - Fortuna, Mario; Silva, Francisco; Medeiros, Ana
Abstract: The present paper analyses the impact of the EU funds, for the European region of Azores, as they affect GDP, employment, and the wellbeing of families in different income levels, using a dynamic, multi‐sector, computable general equilibrium model (CGE) – AzorMod. Simulating the impact of a total cut in transfers and comparing with a base business as usual scenario, it is concluded that the elimination of the EU transfers could cause a sharp permanent fall on public demand and an immediate 2 per cent fall in GDP. The fall in public demand causes a fall in consumer and investment prices which will foster a sharp increase in investment demand that gradually causes GDP to grow back to its initial levels within a ten year period.